2021
DOI: 10.1155/2021/6625548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Annealing and Deformation on Sagging Resistance of a Hot‐Rolled, Four‐Layered Al Alloy Clad Sheet

Abstract: Multilayer brazeable aluminum alloy sheet is prone to collapse during high-temperature brazing process. The sagging resistance of the aluminum composite sheet needs to be further improved for quality control. Effects of annealing and rate of reduction on sagging resistance, microstructure, and Si diffusion of a hot-rolled, four-layered Al clad sheet (4343/3003/6111/3003) were investigated by means of a sagging device, OM, SEM, and TEM. Results showed that once annealed at 360°C, the sagging distance was increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In the manufacturing of heat exchangers, it is necessary that the fin material maintain a certain mechanical strength at a maximum brazing temperature of about 600 • C in order to prevent sagging and deformation, or even cracking during brazing [6,7]. At such high temperatures, aluminum alloys will inevitably undergo phenomena such as recovery, recrystallization, grain growth, second phase particle growth, particle redissolution, intergranular erosion, and slip deformation at grain boundaries, leading to a sharp decline in their mechanical properties [6][7][8][9][22][23][24]. On the other hand, grain boundaries show viscosity at high temperatures, which greatly reduces the resistance to deformation [25].…”
Section: The Influence Of Alloying On the Mechanical Properties Of Al...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the manufacturing of heat exchangers, it is necessary that the fin material maintain a certain mechanical strength at a maximum brazing temperature of about 600 • C in order to prevent sagging and deformation, or even cracking during brazing [6,7]. At such high temperatures, aluminum alloys will inevitably undergo phenomena such as recovery, recrystallization, grain growth, second phase particle growth, particle redissolution, intergranular erosion, and slip deformation at grain boundaries, leading to a sharp decline in their mechanical properties [6][7][8][9][22][23][24]. On the other hand, grain boundaries show viscosity at high temperatures, which greatly reduces the resistance to deformation [25].…”
Section: The Influence Of Alloying On the Mechanical Properties Of Al...mentioning
confidence: 99%
“…On the one hand, good mechanical and sagging resistance properties could be obtained through the optimization of the processing technology. Broer [4] revealed that the mechanical properties resulting from homogenization at lower temperatures could show an increase of approximately 40% compared to the reference homogenization at 550 • C. Kang [9] studied the effects of annealing and deformation on the sagging resistance of 4433/3003/6111/3003 clad sheet, and the results show that low-temperature annealing and a small amount of coarse recrystallized grains could suppress the erosion of Si, resulting in better sagging resistance and strength. On the other hand, alloying to produce dispersed and high-temperature-resistant fine particles is also an effective method to improve high-temperature strengths [11][12][13]26].…”
Section: The Influence Of Alloying On the Mechanical Properties Of Al...mentioning
confidence: 99%
See 1 more Smart Citation